Monitoring the mineralisation of bone nodules in vitro by space- and time-resolved Raman micro-spectroscopy. - Ghita, Adrian; Pascut, Flavius C.; Sottile, Virginie; Notingher, Ioan (Royal Society of Chemistry, 2013)
Raman microscopy was used as a label-free method to study the mineralisation of bone nodules formed by mesenchymal stem cells cultured in osteogenic medium in vitro. Monitoring individual bone nodules over 28 days revealed temporal and spatial changes in the crystalline phase of the hydroxyapatite components of the nodules.